Evaluation of Recently Described Tests for Detection of the Lupus Anticoagulant - Forastiero, Ricardo R; Cerrato, Graciela S; Carreras, Luis O (Thrombosis and Haemostasis, 1994)
It is known that lupus anticoagulants (LA) are antibodies which interfere with phospholipid-dependent coagulation tests, but due to the heterogeneity of LA and the differences in sensitivity of reagents and tests, the diagnosis of LA remains difficult.Recently, Triplett et al. (26) have proposed a new test based on two venoms, Textarin (T) and Ecarin (E), that activate prothrombin but differ in their phospholipid requirements. By testing this new assay we have evaluated 36 patient plasmas containing LA according to standard tests (activated partial thromboplastin time, dilute Russell viper venom time and platelet neutralization procedure) and our results confirm a high sensitivity for LA of the T/E test.In addition, we observed a greater sensitivity of the tissue thromboplastin inhibition test using a recombinant thromboplastin instead of a human placenta thromboplastin.Our study also showed that the T/E test seems to be a useful assay in confirming the diagnosis of LA in patients with an unexplained prolonged APTT.